Pemodelan Numerik Perilaku Lentur Dan Defleksi Elemen Balok Ferrogeopolymer - Bill J. Ebenheazar; Remigildus Cornelis; Partogi H. Simatupang (Universitas Nusa Cendana, 2021)
Ferro-gepolymer is a type of thin-wall reinforced element constructed of geopolymer cement mortar reinforced with closely spaced relatively small diameter mesh in layers. In this investigation, the flexural and the deflection behavior of the ferro-geopolymer beams were determined numerically and the results compared to the experimental values. All the experimental material properties adopted for numerical modeling. The numerical model of all the five beams was 600 mm effective span, 100 mm width, and 100 mm height. Each specimen of the beam model having different layers of wire mesh that are 3, 5, 7, 9, and 11. The results showed that the greater the number of layers, the variation between numerical and experimental results follows the same path without much difference. The numerical result showed that the greater the number of layers, the strength was increases but insignificant.